ChatGPT-style Artificial Intelligence for Financial Applications and Risk Response - Zheng, Zekai (International Journal of Computer Science and Information Technology, 2024)
In an era where artificial intelligence technologies are advancing at a breakneck pace, ChatGPT emerges as a cutting-edge generative pre-trained model, exhibiting immense application potential across a myriad of domains. The financial sector, being at the forefront of technological innovation, is actively exploring the applications of ChatGPT in areas such as customer service, financial analysis, risk management, and personalized product recommendations. However, the advent of these technological applications brings forth a host of concerns, including issues related to data privacy and security, model bias and fairness, challenges in system reliability and transparency, as well as legal and regulatory risks. This paper delves into the current applications of ChatGPT in the financial domain, analyzes the potential risks associated with its deployment, and proposes corresponding risk mitigation strategies. The objective is to provide valuable insights to financial institutions in their endeavor to harness the power of artificial intelligence technologies.